Comparative estimation of effectiveness ratio of switchboards of the third level - Кудзиновская, И. П. (Problems of Informatization and Control, 2009)
Necessity of development of the adequate mathematical models mirroring properties of network processes is considered. The comparative estimation of coefficients of relative efficiency of commutators of the third level in comparison with routers depending on a degree of self-similarity of the traffic and the network loading is received, allowing to draw output on expediency of application of commutators of the third level in modern networks